The Influence Of Social Media Attachment And Brand Identification On Brand Loyalty By Mediation Of Brand Love And Moderation Of Self-Esteem Study On The Indonesian Manufacturing Industry - Guntur Salim; Willy Arafah; Robert Kristaung (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
This research aims to analyze the influence of social media attachment and brand identification on brand love and brand loyalty. The research design used hypothesis testing, using a questionnaire given to 313 respondents. This research was conducted in February 2023 with respondents who were social media users: Facebook, Instagram, Tiktok and Twitter. Data analysis using SPSS and AMOS software. Results: there is a positive and significant influence of consumer-brand identification on brand love, there is a positive and significant influence of social media attachment on brand love, there is a positive and significant influence of brand love on brand loyalty, there is a positive and significant influence of consumer-brand identification on brand loyalty, there is a positive and significant influence of social media attachment on brand loyalty, there is a positive and significant influence of consumer-brand identification on brand loyalty which is mediated by brand love. There is a positive and significant influence of social media attachment on brand loyalty which is mediated by brand love and there is a negative and significant influence of brand love on brand loyalty which is moderated by self-esteem. This research has limitations, quantitative with a survey method and the data collection process took short time with a limited number of respondents, limited to the isotonic drink category, and the market share in Indonesia currently dominated by one particular brand, therefore the source of respondents was also predominantly obtained from consumers of one brand.